Living Qur’an di Pondok Pesantren Mujamma’ Al-Yahya Kamboja - Agimayu, M Singgih; Romadlon, Arif Firdausi Nur; Ridho, Muhammad Mukharom (Journal of Innovation in Teaching and Instructional Media, 2025)
Pesantren (Boarding School) is an important institution in the formation of character and religious values ​​of Muslim society. This study explores the implementation of the concept of “Living Qur’an” and “Living Hadith” at the Mujamma’ Al-Yahya Islamic Boarding School, Cambodia, a country with a Muslim minority context. Using a qualitative field approach, data were collected through observation, in-depth interviews, and documentation. The results of the study indicate that: (1) the Qur’an is read, memorized, and becomes part of the santri’s routine consistently; (2) the tradition of hadith is maintained through oral, written, and social practice expressions; and (3) pesantren instills Islamic educational values ​​such as religiosity, discipline, and the spirit of seeking knowledge. This study contributes to the discourse on contextual Islamic education and provides a unique case study of Islamic pedagogy in a Muslim minority society.